Large intestine as content of congenital inguinal hernia: A case report of intestinal obstruction. (March 2022) - Koirala, Dinesh Prasad; Joshi, Surya Prakash; Timilsina, Sujan; Shress, Vijay; Gc, Saroj; Sharma, Sujan
Abstract: Introduction and importance : Hernias containing appendix, caecum and transverse colon are uncommon in contrast with usual inguinal hernias containing small intestine. The patient usually presents with inguinoscrotal swelling. Case presentation: We present a case of a 2 months old male child presented with inguinoscrotal swelling, vomiting with abdominal distention. On Ultrasonography (USG) of the scrotum, protrusion of the abdominal cavity contents through the right inguinal canal into the scrotum of approximately 3.4 cm × 0.7 cm was found which indicates right inguinal hernia. On the opening of the hernia sac during surgical management, the appendix, caecum and transverse colon were lying inside the hernia sac. Open Herniotomy was performed and the abdomen was closed in layers. Postoperative period of the patient was uneventful. Discussion: Congenital inguinal hernia in the child occurs mostly due to persistent processus vaginalis. History and clinical examination reveals the appearance of lump in the inguinal region or scrotum. Preoperative Ultrasonography can be used to supplement the physical examination and increase the accuracy of its diagnosis. Although the laparoscopic approach is increasingly used nowadays, open hernia repair is preferred in young children. Conclusion: Appendix, caecum and transverse colon are unusual contents of an inguinal hernia. Open herniotomy combined with relieving of the intestinal obstruction is the treatment of choice in young children. Highlights: Large intestinal obstruction in congenital inguinal hernia is a rare presentation. Diagnosis of such obstructed hernias is clinically supplemented by preoperative ultrasonography. Herniotomy along with relief of intestinal obstruction is the mainstay of the treatment.